The Correlation Between Head Circumference and Stature - Rizki Febriawan; Andy Yok Siswosaputro; Novianto Adi Nugroho (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Stature measurement is one of forensic identification examinations. One of evidence that probably found in forensic cases is head circumference. The aim of this research aimed to know the correlation between head circumference and stature. Methods: This research was descriptive analytic with cross-sectional study design. The research was held in Faculty of Medicine Universitas Sebelas Maret with 82 samples of students which consisted of 46 males and 36 females. Independent variable of this research were head circumference ehich was measured with medline. Dependent variable of this research was stature which was measured with microtoise in centimeter. Samples obtained were measured stature and head circumference The result obtained was tested with pearson correlation and simple linear regression test. Results: The statistical analysis result significant correlation between head circumference and stature (r=0,670, p<0,01).The regression equation for stature and head circumference was found to be Y= 6,037 + 2,836 X (R2=0,449). Where Y is the stature of individual and X is the head circumference. Conclusions: There was significant correlation between head circumference and stature.Therefore, the present study will help in medico-legal cases in establishing the identity of an individual. Keywords: Stature, Head circumference